Designer Plasmonic Nanostructures for Unclonable Anticounterfeit Tags. Issue 9 (8th July 2021) - Ibrar, Maha; Skrabalak, Sara E.
Abstract : Counterfeit goods are pervasive in many sectors of our economy, necessitating development of authentication strategies that enhance security of goods and prevent against economic losses. Unique images and barcodes have proven useful but are susceptible to duplication. In contrast, intrinsically random features can be difficult to replicate and represent an alternative if their encoding capacity (EC) is sufficiently high and their analysis facile. Herein, the creation of such anticounterfeit tags with designer plasmonic nanostructures—those whose optical properties are precisely controlled by nanostructure size and shape—as one promising authentication strategy and also reflects on the metrics that define EC as there is a shift toward covert anticounterfeit tags is discussed. Abstract : Intrinsically random features created from plasmonic nanostructures can provide anticounterfeit tags with high encoding capacity by making use of the size‐and shape‐dependent light scattering properties of plasmonic particles and their sensitivity to environmental changes.